PROGRAM REHABILITASI BAGI PENYALAHGUNAAN NARKOTIKA DALAM PERSFEKTI UNDANG-UNDANG NO 35 TAHUN 2009 TENTANG NARKOTIKA - Muhammad Badri (Universitas Batanghari Jambi, 2016)
Narcoticswas nowgrowingexplosiveand has even beenup toon the State ofthetrouble.He spread all over and all levels of society. Act No. 35 in 2009 about the Narcotic is defined that the existence of rehabilitation against the abusers (or recovering) Narcotic contained in article 54. Based on the present article rehabilitation can be organized by the Government or society that is instasi set in a regulation of the Minister, than that at this time the community demands that in the user complete a narcotic which proved to the user judges gave the verdict of the rehabilitation Program of rehabilitation of narcotics is a series of coordinated and integrated effort, consisting of medical efforts, psychosocial guidance, mental, religious, education and exercise Polytechnic to improve adaptability, independence andhelp ourselvesas well as toachievefunctionalcapabilitiesin accordance with thepotential, bothphysical, mental, social and economic.Keyword : rehabilitation,narcotics